The T-box transcription factor Eomes/Tbr2 regulates neurogenesis in the cortical subventricular zone. - Arnold, S; Huang, G; Cheung, A; Era, T; Nishikawa, S; Bikoff, E; Molnár, Z; Robertson, E; Groszer, M (2008)
The embryonic subventricular zone (SVZ) is a critical site for generating cortical projection neurons; however, molecular mechanisms regulating neurogenesis specifically in the SVZ are largely unknown. The transcription factor Eomes/Tbr2 is transiently expressed in cortical SVZ progenitor cells. Here we demonstrate that conditional inactivation of Tbr2 during early brain development causes microcephaly and severe behavioral deficits. In Tbr2 mutants the number of SVZ progenitor cells is reduced and the differentiation of upper cortical layer neurons is disturbed. Neurogenesis in the adult dentate gyrus but not the subependymal zone is abolished. These studies establish Tbr2 as a key regulator of neurogenesis in the SVZ.